Fermented and distilled alcoholic beverages: A technological, chemical and sensory overview: Fermented beverages - De Castilhos, M. Bonatto Machado; Del Bianchi, Vanildo Luiz [UNESP]; Manfroi, Vitor (My University, 2021)
Fermented Beverages presents relevant material regarding fermented alcoholic beverage technologies and their variations, including current information about their chemistry and sensory profiles. The book aims to provide crucial evidence regarding the use of novel technologies in fermented alcoholic beverages and discusses the relationship between chemical and sensory approaches, since both are closely related. This information will be useful for fermented alcoholic beverage producers, scientists and professors, and will be helpful as material for food science, technology and engineering graduate and post-graduate students. This book includes six chapters with the following subject matter: white wines, sparkling wines, cider, mead, beers and craft beers. The distinctiveness of this book lies in the fact that it provides information concerning the use of novel technologies in the fermented alcoholic beverage field, comparing those with classical technologies that have been used worldwide. The book provides useful data regarding the impact of these novel technologies on chemical properties, sensory acceptance and descriptive profiles, with the goal of assessing the changes promoted in the chemical profile of fermented alcoholic beverages as a result of the their quality improvement and sensory uniqueness.